Pengaruh Kualitas Layanan, Kualitas Produk dan Kepuasan Nasabah Terhadap Loyalitas Nasabah PT. Bank Pembiayaan Rakyat Syariah (BPRS) Al-Washliyah Medan - Safriani Safriani; Pani Akhiruddin Siregar (JURNAL ILMIAH EDUNOMIKA, 2024)
The purpose of this research is to investigate and assess the influence of independent factors such as Service Quality (X1), Product Quality (X2), and Customer Satisfaction (X3) on the dependent variable, Customer Loyalty (Y). This research takes a quantitative approach, with sampling done using the Simple Random Sampling technique. The main data utilized in this research came from surveys filled out directly by respondents. The population for this research consisted of 6,171 PT BPRS Al-Washliyah Medan customers, with a sample size of 100. The analytical tool employs several linear regression analyses. The study findings are as follows: 1) The R2 accuracy test results provide an R2 score of 0.785. This means that the R2 value obtained represents the coefficient of determination; 2) The F test results show that the regression model on the independent variables affects the dependent variable concurrently, allowing the independent variable regression model to be used to predict the dependent variable; and 3) The t test results show that Service Quality and Customer Satisfaction have a significant effect on Customer Loyalty. Product Quality has little influence and is not crucial to customer loyalty. Keywords : Service quality, Product quality, Customer Satisfaction, Customer Loyalty